Viewpoint: Responding to Risks and Vulnerability Issues Through Interdisciplinary Curricular Teaching- A case example from the University of Zambia - Justine Lupele; Charles Namafe (Environmental Association of Southern Africa, 2010)
This paper emerges from a keynote presentation at the School of Education, Department of Teacher Education of the University of South Africa Research Indaba in September 2010. The paper introduces the concepts of risks and vulnerability by means of two examples of what happens when development ignores social and environmental impacts. Specifically, it introduces risks and vulnerability in the context of the construction of the Kariba Dam between Zambia and Zimbabwe, and informal settlements in South Africa. It examines what is meant by interdisciplinary approach to curriculum teaching in responding to risks and vulnerability issues. The discussion of interdisciplinary teaching draws on the experience of the University of Zambia which introduced an interdisciplinary taught environmental education undergraduate degree programme. The case of the University of Zambia provides insights into interdisciplinary curricular teaching in environmental and sustainability education. The paper further provides the basis for critical reflections and recommendations on interdisciplinary curricular teaching as a response to risks and vulnerability.